Expression of the sodium iodide symporter in differentiated thyroid cancer - Schmitz, G.; Füzesi, L.; Struck, J.; Siefker, U.; Hamann, A.; Sahlmann, C.-O.; Hüfner, M.; Meller, J. (Nuklearmedizin - NuclearMedicine, 2005)
Aim: Molecular analysis of the expression of the sodium iodide symporter (NIS) in 32 patients with differentiated thyroid cancer (DTC) and correlation with scintigraphic findings (131I,123I) in 19 (59.4%) of them. Patients, methods: NIS expression of 27 primary tumours, 13 lymphnodes and 18 distant metastases was determined by immunostaining using a murine monoclonal anti-NIS-antibody. NIS expression and radionuclide uptake of metastases were analysed by a semiquantitative visual score. Patients were divided into two subgroups: Group 1 (n = 8 patients): indirect correlation of radioiodine uptake (RIU) of subsequent metastases with NIS expression of 7 primary tumours and 3 metastases; Group 2 (n=11 patients): direct correlation of radionuclide uptake with NIS expression of 19 metastases which were excised after imaging. Results: 49 of 58 specimens (84.5%) were NIS-positive. A preserved NIS-expression was found in 12 primary tumours and 8 of 10 (80%) synchrone and 6 of 7 (85.7%) metachrone metastases. Group 1 revealed a 100% positive predictive value (PPV) of a preserved NIS expression in the primary tumour regarding radioiodine uptake in metastases while a lack of NIS expression in the primary tumor did not reliable predict a loss of the metastases’ ability to concentrate radioiodine. In group 2, only 11 of 19 (57.9%) specimens showed a concordant NIS expression and RIU whereas in the remaining 8 cases without visible RIU NIS expression was still present. Conclusions: NIS expression of the primary tumour and metastases in DTC is usually well preserved. We found a positive correlation between NIS expression of the primary and metastatic tissue but could not identify such well correspondence between NIS expression and the RIU of subsequent metastases.
Keywords: Sodium iodide symporter; differentiated thyroid cancer; immunohistochemistry; radioiodine uptake